Type 1 Diabetes: An In-Depth Review of Pathogenesis with a Focus on the Role of Physical Activity and Dietary Interventions - Konopka, Agata; Smołka, Weronika; Skrzypczyk, Marcin; Smółka, Leon (Quality in Sport, 2024)
Introduction: Pompe disease is classified as a metabolic myopathy and is a glycogen storage disorder inherited in an autosomal recessive manner due to a mutation in the gene encoding the enzyme α-glucosidase. There are two main forms: infantile and late-onset. The disease progresses chronically, with clinical presentation characterized by progressive muscle weakness and varying degrees of respiratory insufficiency. Although incurable, causative treatment is available in the form of enzyme replacement therapy with alglucosidase alfa, a human recombinant α-glucosidase. Early diagnosis, primarily based on enzyme activity assessment, is crucial as timely treatment can extend and improve patients' quality of life. Purpose of the work: This study aims to review and characterize the clinical and genetic aspects of Pompe disease. Materials and methods: A comprehensive analysis of research papers available on PubMed, Google Scholar, Web of Science, Embase and Scopus was undertaken using the searchterms encompassing the following keywords: Pompe disease / lysosomal storage disease / myopathy / acid alpha-1,4-glucosidase / glycogen / newborn screening / enzyme replacement therapy. Results: Pompe disease is a life-threatening rare condition where prompt diagnosis is essential due to the availability of causative treatment. It is included in newborn screening programs for inherited metabolic disorders in some countries. Unfortunately, in Poland, routine diagnostic screening does not cover this disease. Implementing screening could simplify diagnosis and reduce the need for extensive differential diagnostics. Diagnosing late-onset Pompe disease can be challenging due to its diverse progression and symptoms. Patients with Pompe disease, even those receiving enzyme replacement therapy, require multidisciplinary care involving cardiology, pulmonology, neurology, and physical therapy.